PENGEMBANGAN KNOWLEDGE MANAGEMENT BUAH DAN TANAMAN OBAT INDONESIA - , ADITYA FIRDI RIZALI; , Sri Suning Kusumawardani, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Relational data model is widely used in applications systems. However, the main obstacle is the lack of dynamic relational model of the model to support knowledge retention as a more concrete and only experts are able to utilize the data model . Therefore, a variation to search for data and information knowledge is limited that is needed to document storage way to knowledge without changing the document format and still keep the data knowledge stored. Representation of knowledge that has been developed in most existing applications using conventional methods have limitations. With the ontology system, knowledge management will be developed more expressive than conventional methods. And this ontology system are expected to exploit the richness and variety of fruits and plants to be used as a herbal medicine. The results of this research is an ontology model of fruit and medicinal plants in the protÃ©gÃ© made in the 2 class which are class fruit and medicinal plants that have a subclass of plant names and plant families as well as the class of diseases that have 18 subclasses disease categories that will be the basis of a representation knowledge management.